BIOM-50. THE IDENTIFICATION AND FUNCTIONAL CHARACTERIZATION OF CIRCULAR RNA CIRC_63706 IN SONIC HEDGEHOG MEDULLOBLASTOMAS. (14th November 2022) - Pokhrel, Rudramani; Katsushima, Keisuke; Stapleton, Stacie; Jallo, George; Raabe, Eric; Eberhart, Charles; Perera, Ranjan
Abstract: Medulloblastoma is a central nervous system tumor that develops through various genetic, epigenetic, and non-coding (nc) RNA-related mechanisms, but the roles played by ncRNAs, particularly circular RNAs (circRNAs), remain poorly defined. CircRNAs are increasingly recognized as stable noncoding RNA therapeutic targets in many cancers, but little is known about their function, subtype specificity, and therapeutic potential in medulloblastomas. To determine medulloblastoma subgroup-specific circRNAs, we subjected RNA-seq data from 175 clinical medulloblastoma samples in four subgroups (SSH, WNT, G3, and G4) to a statistical and machine learning (random forest) pipeline and identified a group of medulloblastoma specific circular RNAs. CircRNA, circ_63706 was identified as sonic hedgehog (SHH) group specific and confirmed its expression by RNA-FISH analysis in clinical tissue samples (tissue microarrays). To identify the molecular function of circ_63706, we depleted circ_63706 in DAOY and ONS76 cells and subjected them to global RNA sequencing and lipid profiling. Circ_63706 resides in the coding gene Pericentrin (PCNT), which is known to be involved in congenital disorders. When Circ_63706 gets depleted by shRNA, it shows a significant decrease in cell proliferation and invasion in SSH cells, and mice implanted with circ_63706 -deleted cells showed reduced tumor growth and extended survival compared to parental cells implant. At the molecular level, we identified circ_63706 -deleted cells elevated total ceramide and oxidized lipids and reduced total triglyceride (TG). Our study implicates an identification of a novel oncogenic circular RNA in the medulloblastoma subgroup SSH and establishes its potential as a future therapeutic target.